HUBUNGAN PRODUKSI URIN DENGAN SATURASI OKSIGEN TERHADAP KEMATIAN SELAMA PERAWATAN PASIEN GAGAL JANTUNG AKUT - AZZUHRA PERMATA KHAIRA; AHMAD HANDAYANI (LP2MTBM MAKARIOZ, 2021)
Acute heart failure has manifestations with rapid onset that needs to be treated in within 24 hours. Urine output and oxygensaturation (SpO2) are used to monitor patients in the ICU to determine the severity and prognosis ot the disease. This studyaims to determine the relationship between urine output and oxygen saturation to the death of patients during treatment.This study used analytical method with cross sectional design. The number of sample is 45, and the secondary data wascollected from the hospitals’ medical records. The results showed that the relationship of urine output with patients’ outcomeshowed a p value of 0.011 (p <0.05). While the relationship of oxygen saturation with outcome and the relationship of urineoutput with oxygen saturation both showed p values of 0.123 and 0.368 (p>0.05). There is a significant relationship betweenurine output and the acute heart failure patients’ outcome.